Innovative Pedagogies for Teaching the Arts in Thailand: An Interdisciplinary Approach to Cultural Preservation and Digital Media - Choeirod, Ratchaneechay (Journal of Exploration in Interdisciplinary Methodologies (JEIM), 2025)
This paper explores innovative pedagogical approaches for teaching the arts in Thailand, focusing on integrating interdisciplinary methods with digital media to preserve and revitalize cultural heritage. As globalization and technological advancements reshape education, traditional art teaching methods struggle to engage contemporary students. This study examines how emerging pedagogies - incorporating artificial intelligence (AI), virtual reality (VR), and multimedia - enhance learning outcomes while fostering cultural appreciation. By integrating digital media into arts education, educators can create immersive and interactive experiences that bridge traditional art forms with modern technologies. The research highlights the necessity of interdisciplinary approaches, where subjects like history, music, and performance arts converge to enrich students’ understanding of Thai cultural identity. Digital platforms facilitate access to artistic traditions, allowing students to interact with cultural narratives through virtual museums, augmented reality applications, and online collaborative projects. Case studies demonstrate how technology aids in safeguarding intangible cultural heritage while enabling creative expression through digital storytelling and multimedia art forms. Additionally, the study investigates the challenges and limitations of implementing these innovative pedagogies, including disparities in technological access, teacher training gaps, and concerns over cultural authenticity in digital adaptation. To address these issues, the paper advocates for curriculum reforms that balance tradition and innovation, professional development for educators in digital arts integration, and policies supporting sustainable arts education. By leveraging technology-driven teaching methods, Thai arts education can maintain its relevance in a rapidly evolving world while ensuring that cultural heritage remains an integral part of students’ learning experiences. This research contributes to ongoing discussions on the role of education in cultural conservation and underscores the potential of digital media as a transformative tool in the arts. Ultimately, the findings reinforce the significance of interdisciplinary and technology-enhanced learning strategies in fostering a deeper appreciation of Thai artistic heritage among future generations.